Preparation method of polytetrafluoroethylene composite film for friction nano generator

The method addresses the challenges of complex processes and poor dispersion in PTFE composite membrane production by using a hydrophobic conductive filler and interface modifier, achieving uniform and high-performance membranes suitable for large-scale production and efficient power generation.

CN119239012APending Publication Date: 2025-01-03SICHUAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310798675.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-03
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Existing methods for preparing polytetrafluoroethylene (PTFE) composite membrane materials for triboelectric nanogenerators face challenges such as complex processes, high costs, poor filler dispersion, agglomeration, and inability to achieve uniformity and large-scale production, leading to structural defects and low friction power generation efficiency.

Method used

A method involving the use of a hydrophobic conductive filler, an interface modifier, and a synergist to form a composite filler slurry, which is then mixed with PTFE dispersion for film formation, drying, and sintering, without additional filler surface treatment, to achieve stable dispersion and improved interface bonding, resulting in a uniform and high-performance PTFE composite membrane.

Benefits of technology

The method enables uniform dispersion of conductive fillers, reduces defects, enhances mechanical strength, and allows for large-scale production of PTFE composite membranes with high friction power generation efficiency and excellent mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention provides a preparation method of a polytetrafluoroethylene composite film for a friction nano-generator. The preparation method comprises the following steps: preparing composite filler slurry, mixing polytetrafluoroethylene dispersion liquid with the composite filler slurry, and then performing film-forming drying, sinter molding and rolling to prepare the polytetrafluoroethylene composite film. The polytetrafluoroethylene composite membrane material provided by the invention has the characteristics of high friction power generation efficiency, excellent mechanical properties, good membrane structure uniformity and stability, flexibly adjustable thickness, large breadth and simple and feasible preparation process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for preparing a polytetrafluoroethylene composite membrane material, and more specifically to a method for preparing a polytetrafluoroethylene composite membrane using a polytetrafluoroethylene dispersion as a raw material, which has the advantages of thin thickness, good uniformity, controllable structure, large width, good dimensional stability, excellent performance, simple equipment and process, and can realize large-scale industrial production. The method belongs to the technical field of high-performance polytetrafluoroethylene composite membrane material preparation. Background Art

[0002] The rapid explosive growth of mobile portable wearable electronic devices in recent years has put forward higher requirements for the lightweight, miniaturization and flexibility of electronic energy devices. As soon as the triboelectric nanogenerator (TENG), a new energy harvesting technology, appeared, it immediately attracted the attention of scholars around the world. It can collect a large amount of micro energy in nature, such as water waves, micro wind, sound waves and human body movements, and convert them into electrical energy.

[0003] Polytetrafluoroethylene (PTFE) is the most important fluorine-containing polymer, which is polymerized from tetrafluoroethylene. The molecular chain of PTFE is composed of carbon-fluorine units arranged in a strict alternating pattern, with a helical configuration as a whole and a highly symmetrical molecular structure. The carbon atoms are coated by F atoms with a small radius and high electronegativity. The CF bond has a high bond energy (460 kJ / mol) and a short bond distance. Therefore, PTFE has outstanding dielectric properties, chemical corrosion resistance, lubricity and weather resistance. The CF bond of PTFE has a strong electron-withdrawing effect, making it one of the most electronegative materials currently available. PTFE also has excellent weather resistance and stability, making it a very promising triboelectric material.

[0004] If conductive functional fillers can be added to PTFE, prepared into composite functional membrane materials, and used to prepare friction nanogenerators, the functional application of PTFE membrane materials can be realized, further enhancing its application value. However, due to the extremely low surface energy of PTFE, it is extremely difficult to form a good interface interaction with the conductive functional filler, and it is easy to have problems such as uneven dispersion of the filler, easy agglomeration, low friction power generation efficiency, and decreased mechanical properties. Although some scholars have prepared conductive functional fillers by themselves and performed filler surface treatment to improve the dispersion of conductive functional fillers in PTFE, the preparation and surface treatment of functional fillers are cumbersome and costly, and cannot be applied to mass production. On the other hand, traditional PTFE membrane preparation methods such as turning and calendering are mostly used to prepare pure PTFE membrane materials. The multi-dimensional force fields such as pressure and shear force in the preparation process can easily cause PTFE to debond with the filler surface to produce interface defects, and it is impossible to obtain a structurally complete and uniform TFE composite functional membrane material. It is necessary to develop a new method for preparing PTFE composite membrane materials filled with conductive functional fillers.

[0005] Therefore, with the development of miniaturization and lightweight of electronic devices and wearable devices, it is very necessary to develop a method that can use commercial conductive functional fillers and simple molding processes to prepare PTFE composite functional membrane materials with good triboelectric power generation efficiency, so as to overcome the shortcomings of the existing technology, such as complicated process, high cost, easy to produce micro defects, and inability to achieve mass production. Summary of the invention

[0006] In view of the shortcomings of the existing preparation methods of PTFE composite functional membrane materials for friction nanogenerators, the purpose of the present invention is to propose a preparation method of PTFE composite functional membrane materials with PTFE dispersion as the main raw material. The method first mixes the interface modifier, the synergist and the hydrophobic conductive functional filler into a composite filler slurry to form a pre-impregnation and dispersion of the conductive functional filler, and then adds the composite filler slurry into the polytetrafluoroethylene dispersion for mixing and dispersion, and prepares the PTFE composite functional membrane material through film formation, drying and sintering. This also becomes a key technical means to improve the dispersibility and interface bonding of the filler in PTFE without additional surface modification of the filler, and to improve the friction power generation efficiency of the PTFE composite membrane. The prepared PTFE composite membrane material has high friction power generation efficiency, uniform thickness, large width, controllable structure, and high mechanical strength. At the same time, the method has the advantages of cheap and easy-to-obtain raw materials, simple preparation process, and can realize large-scale industrial production.

[0007] The basic principle of the present invention is: in view of the shortcomings of the existing PTFE composite membrane materials for tribo-nanoelectric power generation, such as complicated preparation process, high cost, and inability to be applied to mass production, and the disadvantages of the traditional PTFE film making methods such as turning and calendering, which easily cause the PTFE and the filler surface to debond and produce interface defects, and thus fail to produce a structurally complete and uniform TFE composite functional membrane material, the present invention firstly utilizes the "like dissolves like" principle to mix an oily liquid interface modifier with a conductive functional filler having hydrophobic and lipophilic properties to form a composite filler slurry, and adds a synergist to increase the wetting and dispersion effect of the conductive functional filler, and then The composite filler slurry is added to the PTFE dispersion. The interfacial modifier is immiscible with water but has good affinity with the PTFE particles in the PTFE dispersion. On the one hand, the interfacial modifier forms a stable liquid bridge between the PTFE particles through the action of interfacial tension and capillary force, thereby forming a three-dimensional physical network connected by liquid bridges in the PTFE dispersion and significantly improving the film-forming property of the PTFE composite dispersion. On the other hand, since the conductive functional filler is stably dispersed in the interfacial modifier, as the interfacial modifier infiltrates the surface of the PTFE particles, the conductive functional filler is also stably and well dispersed in the PTFE dispersion (such as the attached Figure 1 As shown), a PTFE composite dispersion liquid in which the conductive functional filler is stably dispersed is formed. In the subsequent film-forming drying and sintering molding process, the conductive functional filler can also be stably dispersed in the PTFE. Therefore, there is no need to perform additional surface treatment on the filler. Only commercially available hydrophobic conductive functional fillers can be used to achieve uniform dispersion of the conductive functional filler in PTFE, and the successful preparation of PTFE composite membrane materials for friction nanogenerators. In addition, the use of polytetrafluoroethylene dispersion liquid to prepare PTFE composite membrane materials by casting and other methods does not have the strong stress of traditional PTFE turning or calendering, the interface between PTFE and the filler will not be damaged during the molding process, the composite membrane material has fewer defects, and the structural uniformity is high, which can significantly improve the comprehensive performance of the PTFE composite membrane material.

[0008] The present invention is based on the above principle and the technical solution adopted to achieve the above invention object is: adding a hydrophobic conductive functional filler to an interface modifier and a synergist to prepare a composite filler slurry, then adding it to a polytetrafluoroethylene dispersion, and preparing a polytetrafluoroethylene composite film through mixing and dispersion, film forming and drying, sintering and winding, characterized in that: (1) The molecular weight of polytetrafluoroethylene in the polytetrafluoroethylene dispersion is 500,000 to 2,000,000, and the particle size of polytetrafluoroethylene latex is 150 to 220 nanometers; (2) The interface modifier is a non-polar liquid with a molecular weight of less than 1000 and a three-phase contact angle with polytetrafluoroethylene particles and water of less than 90 degrees and is immiscible with water, including polyorganosiloxanes with a molecular weight of less than 1000, long-chain alkanes, fatty alcohols and aromatic alcohols, such as a mixture of one or more of silicone oil, white oil, n-dodecane, octadecanol and terpineol, and the added mass is 0.01-5% of the solid mass in the polytetrafluoroethylene dispersion; (3) The synergist is an oil-soluble material that can increase the viscosity of the above-mentioned interface modifier and is immiscible with water, such as a mixture of one or more of modified hydrogenated castor oil, organic bentonite, hydrophobically modified acrylate, polyisobutylene, polymethacrylate, and ethylene-propylene copolymer, and the added mass is 0-5% of the mass of the interface modifier; (4) The hydrophobic conductive functional filler is a zero-dimensional or two-dimensional conductive functional filler having a hydrophilic contact angle greater than 90 degrees and a conductivity greater than 10 S / m, such as a mixture of one or more of conductive carbon black, silver powder, graphene, and conductive graphite sheets, and the added mass is 0.01-10% of the solid mass in the polytetrafluoroethylene dispersion; (5) The composite filler slurry is prepared by adding an interface modifier, a synergist and a hydrophobic conductive functional filler into a planetary agitator and stirring at a speed of 1000 to 2000 revolutions per minute for 2 to 10 minutes; (6) The mixing and dispersing process comprises the following steps: adding a composite filler slurry to a polytetrafluoroethylene dispersion, stirring the mixture at a speed of 1000 to 2000 revolutions per minute for 2 to 10 minutes using a propeller or planetary agitator, and then stirring the mixture at a speed of 500 to 800 revolutions per minute for 2 to 10 minutes to prepare a polytetrafluoroethylene composite dispersion; (7) The film-forming and drying step is to cast, scrape or spin coat the polytetrafluoroethylene composite dispersion on a suitable substrate material and dry it at a suitable temperature; (8) The polytetrafluoroethylene composite film can be completely peeled off from the base material and rolled up, and the film thickness ranges from 5 to 200 microns.

[0009] The reason why polytetrafluoroethylene with a molecular weight of 500,000 to 2 million is chosen is that polytetrafluoroethylene with a molecular weight that is too small cannot achieve practical film mechanical strength, and a molecular weight that is too large will lead to excessive melt viscosity and difficulty in film formation; the polytetrafluoroethylene latex particle size is 150 to 220 nanometers because a latex particle size that is too small will increase the size of film defects, and a particle size that is too large will be detrimental to the storage stability of the dispersion.

[0010] Silicone oil, paraffin oil, white oil, n-dodecane, octadecyl alcohol, pinene alcohol and other non-polar liquids with a three-phase contact angle of less than 90 degrees with PTFE latex particles and water, immiscible with water and with a molecular weight less than 1000 are selected because after the above non-polar liquids are dispersed in the polytetrafluoroethylene dispersion, small droplets will be formed under stirring. Since the three-phase contact angle of the non-polar liquids with PTFE particles and water is less than 90 degrees, the non-polar liquids have a stronger wettability to the polytetrafluoroethylene particles than water, and will be connected between the polytetrafluoroethylene particles and remain stable, forming a three-dimensional physical network throughout the PTFE dispersion, which will increase the interaction between the polytetrafluoroethylene particles during film formation and improve the defects formed in the polytetrafluoroethylene film during the drying process.

[0011] Modified hydrogenated castor oil, organic bentonite, hydrophobically modified acrylate, polyisobutylene, polymethacrylate, ethylene propylene copolymer and the like are selected as synergists, which are oil-soluble materials that can increase the viscosity of the above-mentioned interface modifiers and are immiscible with water, because on the one hand, they can improve the dispersion effect of the hydrophobic conductive functional filler, and on the other hand, since commercially available polytetrafluoroethylene dispersions generally contain surfactants, the presence of which will weaken the effect of the interface modifier, so the synergist is added to the interface modifier to enhance the interface wettability between the interface modifier and the PTFE particles.

[0012] The particle size range of the hydrophobic conductive functional filler is limited because within the preferred filler particle size range, it has a better dispersion effect with the PTFE dispersion.

[0013] The film forming drying temperature is selected to be 20-80 degrees Celsius, the drying time is 5-60 minutes, the sintering molding temperature is selected to be 350-400 degrees Celsius, and the sintering molding time is 10-60 minutes. The obtained polytetrafluoroethylene film can be up to 1.5 meters wide and 1000 meters long.

[0014] Compared with the existing technology for preparing polytetrafluoroethylene membrane materials, the present invention has the following outstanding advantages: The present invention proposes a method for preparing a polytetrafluoroethylene composite membrane for a friction nanogenerator using a polytetrafluoroethylene dispersion, which does not require additional surface treatment of the filler and only uses commercially available hydrophobic conductive functional fillers to achieve uniform dispersion of the conductive functional filler in PTFE and successful preparation of the PTFE composite membrane material for the friction nanogenerator; The present invention proposes a method for preparing a polytetrafluoroethylene composite membrane for a friction nanogenerator using a polytetrafluoroethylene dispersion. The film forming, drying, sintering and winding of the PTFE composite dispersion are continuously performed. The drying time is as short as 5 minutes, and the molding time is as short as 10 minutes. The shortcomings of the traditional PTFE membrane material turning or calendering preparation process, which is complicated, time-consuming and equipment-intensive, are overcome. The process is simple, time-saving and large-scale continuous production can be achieved. The present invention proposes a method for preparing a polytetrafluoroethylene composite film for a friction nanogenerator using a polytetrafluoroethylene dispersion. The entire preparation process has no strong stress, and the film is sintered in a thin film state. The film itself is heated evenly and there is no temperature gradient inside and outside the film. Therefore, the prepared film has higher uniformity, less internal stress, and stronger interface between PTFE and filler particles than the film product prepared by turning, and has excellent long-term use performance, mechanical properties and high friction power generation efficiency. The present invention proposes a method for preparing a polytetrafluoroethylene composite film for a friction nanogenerator using a polytetrafluoroethylene dispersion, wherein the film thickness can be as low as 5 microns, which is suitable for the current demand for ultra-thin and high-performance PTFE composite functional membrane materials, and the film thickness can be accurately controlled within the range of 5 to 200 microns by adjusting the single coating thickness and multiple coatings, and the film thickness uniformity is good; The present invention proposes a method for preparing a polytetrafluoroethylene composite film for a friction nanogenerator using a polytetrafluoroethylene dispersion, wherein the interface modifier used can be removed by volatilization or degradation during the drying process, and will not produce residues and will not affect other properties of the composite material. The obtained PTFE composite dispersion has high storage stability and is difficult to produce stratification phenomenon. The preparation method proposed by the invention has strong operability and feasibility. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 The figure shows the dispersion of hydrophobic conductive carbon black in PTFE dispersion without adding interfacial modifier (a) and the dispersion of hydrophobic conductive carbon black in PTFE dispersion with adding interfacial modifier (b).

[0016] Figure 2 Flow chart for preparing polytetrafluoroethylene composite membrane materials.

[0017] Figure 3 This is a photo of the PTFE composite membrane material prepared in Example 1. DETAILED DESCRIPTION

[0018] The present invention is further described in detail below by way of examples. In the following examples, the amount of each component is by mass. It is necessary to point out here that the following examples are only further explanations of the present invention and cannot be construed as limiting the scope of protection of the present invention. Those skilled in the art can make some non-essential improvements and adjustments to the present invention based on the above-mentioned content of the present invention.

[0019] Example 1 Content of each component by weight: Component mass fraction Polytetrafluoroethylene dispersion (Shandong Dongyue Polymer Materials Co., Ltd.) 100 Octadecanol (analytical grade) 0.15 Conductive carbon black (average particle size 500nm) 1 The first step is to prepare the materials according to the above proportions; the second step is to add conductive carbon black to octadecyl alcohol, use a planetary agitator to stir at a high speed of 1000 revolutions per minute for 8 minutes to obtain a composite filler slurry, and then add it to a polytetrafluoroethylene dispersion, use a planetary agitator to stir at a high speed of 1000 revolutions per minute for 10 minutes, and then stir at a low speed of 600 revolutions per minute for 10 minutes to prepare a polytetrafluoroethylene composite dispersion; the third step is to cast the polytetrafluoroethylene composite dispersion on a substrate, dry it at 40°C for 10 minutes, and then sinter it at 365°C for 15 minutes to form it; the fourth step is to peel off the sintered film from the substrate, and the obtained polytetrafluoroethylene composite film has a thickness of 5 microns and a width of 120 cm.

[0020] like Figure 1 As shown in the figure, if no interfacial modifier is added, the hydrophobic conductive carbon black cannot be dispersed in the aqueous polytetrafluoroethylene dispersion, and the PTFE composite membrane material cannot be prepared for comparison. But this also illustrates the importance of adding an interfacial modifier. Only by adding an interfacial modifier can the commercially available hydrophobic conductive carbon black be uniformly dispersed in the PTFE dispersion and the PTFE composite dispersion form a good film without additional filler surface treatment.

[0021] Comparative Example 1 In order to verify the effect of the interface modifier, the interface modifier in Example 1 was replaced with sodium dodecyl sulfate, a surfactant commonly used in the industry, and a polytetrafluoroethylene composite membrane material having the same thickness, the same drying and sintering process as Example 1 was obtained as Comparative Example 1.

[0022] Comparative Example 1: Content of each component by weight: Component mass fraction Polytetrafluoroethylene dispersion (Shandong Dongyue Polymer Materials Co., Ltd.) 100 Sodium dodecyl sulfate (analytical grade) 0.15 Conductive carbon black (average particle size 500nm) 1 In this embodiment, octadecyl alcohol is used as an interface modifier. The surface of the polytetrafluoroethylene composite film prepared after cast coating, drying and sintering has no defects and good thickness uniformity. The thickness is tested to be 5 microns ± 0.2 microns. The thickness of the PTFE composite film prepared in Comparative Example 1 is tested to be 5 microns ± 0.8 microns. In addition, void defects caused by the agglomeration of conductive functional fillers can be observed on the surface of the polytetrafluoroethylene composite film prepared in Comparative Example 1, and a membrane material with a width of 120 cm cannot be prepared. The polytetrafluoroethylene composite film was brittlely broken using liquid nitrogen and its interface was observed by scanning electron microscopy. The results show that the conductive functional fillers in the polytetrafluoroethylene composite film prepared in this embodiment are evenly dispersed without obvious agglomeration, and the interior of the film is uniform and dense. In the polytetrafluoroethylene composite film prepared in Comparative Example 1, agglomeration of fillers is observed, and there are voids inside the film, which shows that the polytetrafluoroethylene composite film prepared in this embodiment has good structural uniformity. The tensile properties were tested by a universal mechanical testing machine. The results showed that the tensile strength was increased from 7.1MPa in comparative example 1 to 22.7MPa, and the elongation at break was increased from 16% to 185%. A triboelectric nanogenerator model based on a polytetrafluoroethylene composite membrane with an area of ​​20mm×20mm was made using a polytetrafluoroethylene composite membrane and a bacterial cellulose film as electrodes, respectively. The triboelectric power generation performance was tested by a linear motor and an electrostatic meter. The results showed that the triboelectric nanogenerator based on the composite membrane of this embodiment had an open circuit voltage of 200V and a short circuit current of 11μA. The values ​​and membrane state were stable after 100 repetitions. The triboelectric nanogenerator based on the composite membrane of comparative example 1 had an open circuit voltage of 50V and a short circuit current of 6μA, and the membrane was damaged after several experiments, which was mainly caused by micro defects inside the film. It shows that the polytetrafluoroethylene composite membrane prepared in this embodiment has good triboelectric power generation efficiency.

[0023] Example 2 Content of each component by weight: Component mass fraction Polytetrafluoroethylene dispersion (Shandong Dongyue Polymer Materials Co., Ltd.) 100 Octadecanol (analytical grade) 0.2 Conductive carbon black (average particle size 500nm) 1 Silver powder (average particle size 100nm) 0.5 The first step is to prepare the materials according to the above proportions; the second step is to add conductive carbon black and silver powder to octadecyl alcohol, use a planetary stirrer to stir at a speed of 1500 revolutions per minute for 8 minutes to obtain a composite filler slurry, and then add it to a polytetrafluoroethylene dispersion, use a planetary stirrer to stir at a speed of 1500 revolutions per minute for 8 minutes, and then stir at a low speed of 800 revolutions per minute for 8 minutes to prepare a polytetrafluoroethylene composite dispersion; the third step is to cast the polytetrafluoroethylene composite dispersion on a substrate, dry it at 60°C for 12 minutes, and then sinter it at 370°C for 15 minutes to form it; the fourth step is to peel off the sintered film from the substrate, and the obtained polytetrafluoroethylene composite film has a thickness of 8 microns and a width of 150 cm.

[0024] If no interfacial modifier is added, the hydrophobic conductive carbon black and silver powder cannot be dispersed in the aqueous polytetrafluoroethylene dispersion, and the PTFE composite membrane material cannot be prepared for comparison. But this also illustrates the importance of adding an interfacial modifier. Only by adding an interfacial modifier can the commercially available hydrophobic conductive carbon black and silver powder be uniformly dispersed in the PTFE dispersion without additional filler surface treatment, and the PTFE composite dispersion can form a good film.

[0025] Comparative Example 2 In order to verify the effect of the interface modifier, the interface modifier in Example 2 was replaced with sodium dodecyl sulfate, a surfactant commonly used in the industry, and a polytetrafluoroethylene composite membrane material having the same thickness, the same drying and sintering process as Example 2 was obtained as Comparative Example 2.

[0026] Comparative Example 2: Content of each component by weight: Component mass fraction Polytetrafluoroethylene dispersion (Shandong Dongyue Polymer Materials Co., Ltd.) 100 Sodium dodecyl sulfate (analytical grade) 0.2 Conductive carbon black (average particle size 500nm) 1 Silver powder (average particle size 100nm) 0.5 The present embodiment adopts octadecyl alcohol as the interface modifier, and the polytetrafluoroethylene composite film prepared after the casting coating drying and sintering has no surface defects and good thickness uniformity, and the thickness is tested to be 8 microns ± 0.18 microns, and the thickness of the PTFE composite film prepared in Comparative Example 2 is tested to be 8 microns ± 1.2 microns. In addition, the surface of the polytetrafluoroethylene composite film prepared in Comparative Example 2 can be observed to have hollow defects caused by the agglomeration of conductive functional fillers, and it is impossible to prepare a film material with a width of 150 cm. This shows that the polytetrafluoroethylene composite film prepared in this embodiment has good structural uniformity. The tensile properties were tested by a universal mechanical testing machine, and the results showed that its tensile strength was increased from 6.8MPa in Comparative Example 2 to 21.9MPa, and the elongation at break was increased from 16% to 192%. A triboelectric nanogenerator model based on a polytetrafluoroethylene composite membrane with an area of ​​20 mm × 20 mm was made using a polytetrafluoroethylene composite membrane and a bacterial cellulose film as electrodes, respectively. The triboelectric nanogenerator model based on the polytetrafluoroethylene composite membrane was tested by a linear motor and an electrometer. The results showed that the open circuit voltage of the triboelectric nanogenerator based on the composite membrane of this embodiment was 240 V, the short circuit current was 17 μA, and the value and membrane state were stable after 100 repetitions. The open circuit voltage of the triboelectric nanogenerator based on the composite membrane of Comparative Example 2 was 45 V, the short circuit current was 5.8 μA, and the membrane was damaged after several experiments, which was mainly caused by micro defects inside the film. It shows that the polytetrafluoroethylene composite membrane prepared in this embodiment has good triboelectric efficiency.

[0027] Example 3 Content of each component by weight: Component mass fraction Polytetrafluoroethylene dispersion (Shandong Dongyue Polymer Materials Co., Ltd.) 100 n-Dodecane (analytical grade) 0.2 Polyisobutylene (molecular weight 5000) 0.003 Graphene (average particle size: length: 100nm, width: 100nm) 1.2 The first step is to prepare the materials according to the above proportions; the second step is to add graphene to n-dodecane and polyisobutylene, use a planetary agitator to stir at a speed of 1800 revolutions per minute for 10 minutes to obtain a composite filler slurry, and then add it to a polytetrafluoroethylene dispersion, use a planetary agitator to stir at a speed of 1800 revolutions per minute for 10 minutes, and then stir at a low speed of 600 revolutions per minute for 5 minutes to prepare a polytetrafluoroethylene composite dispersion; the third step is to cast the polytetrafluoroethylene composite dispersion on a substrate, dry it at 80°C for 6 minutes, and then sinter it at 375°C for 12 minutes to form it; the fourth step is to peel off the sintered film from the substrate, and the obtained polytetrafluoroethylene composite film has a thickness of 10 microns and a width of 130 cm.

[0028] If no interfacial modifier is added, graphene cannot be dispersed in the aqueous polytetrafluoroethylene dispersion, and PTFE composite membrane materials cannot be prepared for comparison. But this also illustrates the importance of adding an interfacial modifier. Only by adding an interfacial modifier can the uniform dispersion of commercially available hydrophobic graphene in the PTFE dispersion and the good film formation of the PTFE composite dispersion be achieved without additional filler surface treatment.

[0029] Comparative Example 3 In order to verify the effect of the interface modifier, the interface modifier in Example 3 was replaced with sodium dodecyl sulfate, a surfactant commonly used in the industry, and a polytetrafluoroethylene composite membrane material having the same thickness, the same drying and sintering process as Example 3 was obtained as Comparative Example 3.

[0030] Comparative Example 3: Content of each component by weight: Component mass fraction Polytetrafluoroethylene dispersion (Shandong Dongyue Polymer Materials Co., Ltd.) 100 Sodium dodecyl sulfate (analytical grade) 0.2 Polyisobutylene (molecular weight 5000) 0.003 Graphene (average particle size: length: 100nm, width: 100nm) 1.2 This embodiment uses n-dodecane as an interface modifier. The polytetrafluoroethylene composite film prepared after cast coating, drying and sintering has no surface defects and good thickness uniformity. The thickness is tested to be 10 microns ± 0.08 microns. The thickness of the PTFE composite film prepared in Comparative Example 3 is tested to be 10 microns ± 1.0 microns. In addition, the surface of the polytetrafluoroethylene composite film prepared in Comparative Example 3 can be observed to have void defects caused by the agglomeration of conductive functional fillers, and a membrane material with a width of 130 cm cannot be prepared. This shows that the polytetrafluoroethylene composite film prepared in this embodiment has good structural uniformity. The tensile properties were tested by a universal mechanical testing machine. The results showed that its tensile strength was increased from 9.6MPa in Comparative Example 3 to 29.7MPa, and the elongation at break was increased from 36% to 241%. A triboelectric nanogenerator model based on a polytetrafluoroethylene composite membrane with an area of ​​20 mm × 20 mm was made using a polytetrafluoroethylene composite membrane and a bacterial cellulose film as electrodes, respectively. The triboelectric nanogenerator model based on the polytetrafluoroethylene composite membrane was tested by a linear motor and an electrometer. The results showed that the open circuit voltage of the triboelectric nanogenerator based on the composite membrane of this embodiment was 260 V, the short circuit current was 19 μA, and the value and membrane state were stable after 100 repetitions. The open circuit voltage of the triboelectric nanogenerator based on the composite membrane of Comparative Example 3 was 58 V, the short circuit current was 6.2 μA, and the membrane was damaged after several experiments, which was mainly caused by micro defects inside the film. It shows that the polytetrafluoroethylene composite membrane prepared in this embodiment has good triboelectric efficiency.

[0031] Example 4 Content of each component by weight: Component mass fraction Polytetrafluoroethylene dispersion (Shandong Dongyue Polymer Materials Co., Ltd.) 100 n-Dodecane (analytical grade) 0.2 Ethylene propylene copolymer (molecular weight 600) 0.004 Conductive graphite flakes (average particle size: length: 200nm, width: 200nm) 1 Conductive carbon black (average particle size 50nm) 0.5 The first step is to prepare the materials according to the above proportions; the second step is to add the conductive graphite sheet and the conductive carbon black to n-dodecane and ethylene propylene copolymer, use a planetary stirrer to stir at a speed of 2000 revolutions per minute for 6 minutes to obtain a composite filler slurry, and then add it to a polytetrafluoroethylene dispersion, use a planetary stirrer to stir at a speed of 2000 revolutions per minute for 6 minutes, and then stir at a low speed of 600 revolutions per minute for 3 minutes to prepare a polytetrafluoroethylene composite dispersion; the third step is to cast the polytetrafluoroethylene composite dispersion on a substrate, dry it at 60°C for 10 minutes, and then sinter it at 375°C for 12 minutes to form it; the fourth step is to peel off the sintered film from the substrate, and the obtained polytetrafluoroethylene composite film has a thickness of 5 microns and a width of 120 cm.

[0032] If no interfacial modifier is added, the conductive graphite flakes and conductive carbon black cannot be dispersed in the aqueous polytetrafluoroethylene dispersion, and the PTFE composite membrane material cannot be prepared for comparison. But this also illustrates the importance of adding an interfacial modifier. Only by adding an interfacial modifier can the commercially available conductive graphite flakes and conductive carbon black be uniformly dispersed in the PTFE dispersion without additional filler surface treatment, and the PTFE composite dispersion can form a good film.

[0033] Comparative Example 4 In order to verify the effect of the interface modifier, the interface modifier in Example 4 was replaced with sodium dodecyl sulfate, a surfactant commonly used in the industry, and a polytetrafluoroethylene composite membrane material having the same thickness, the same drying and sintering process as Example 4 was obtained as Comparative Example 4.

[0034] Comparative Example 4: Content of each component by weight: Component mass fraction Polytetrafluoroethylene dispersion (Shandong Dongyue Polymer Materials Co., Ltd.) 100 Sodium dodecyl sulfate (analytical grade) 0.2 Ethylene propylene copolymer (molecular weight 600) 0.004 Conductive graphite flakes (average particle size: length: 200nm, width: 200nm) 1 Conductive carbon black (average particle size 50nm) 0.5 This embodiment uses n-dodecane as an interface modifier. The polytetrafluoroethylene composite film prepared after casting, coating, drying and sintering has no surface defects and good thickness uniformity. The thickness is tested to be 5 microns ± 0.05 microns. The thickness of the PTFE composite film prepared in Comparative Example 4 is tested to be 5 microns ± 0.40 microns. In addition, the surface of the polytetrafluoroethylene composite film prepared in Comparative Example 4 can be observed to have void defects caused by the agglomeration of conductive functional fillers, and a membrane material with a width of 120 cm cannot be prepared. This shows that the polytetrafluoroethylene composite film prepared in this embodiment has good structural uniformity. The tensile properties were tested by a universal mechanical testing machine. The results showed that its tensile strength was increased from 8.9MPa in Comparative Example 4 to 28.6MPa, and the elongation at break was increased from 31% to 247%. A triboelectric nanogenerator model based on a polytetrafluoroethylene composite membrane with an area of ​​20 mm × 20 mm was made using a polytetrafluoroethylene composite membrane and a bacterial cellulose film as electrodes, respectively. The triboelectric nanogenerator model based on the polytetrafluoroethylene composite membrane was tested by a linear motor and an electrometer. The results showed that the triboelectric nanogenerator based on the composite membrane of this embodiment had an open circuit voltage of 265 V and a short circuit current of 20 μA. The values ​​and membrane state were stable after 100 repetitions. The triboelectric nanogenerator based on the composite membrane of Comparative Example 4 had an open circuit voltage of 51 V and a short circuit current of 6.1 μA, and the membrane was damaged after several experiments, which was mainly caused by micro defects inside the film. This shows that the polytetrafluoroethylene composite membrane prepared in this embodiment has good triboelectric efficiency.

Claims

1. A method for preparing a polytetrafluoroethylene composite membrane for a friction nanogenerator, comprising adding a hydrophobic conductive functional filler to an interface modifier and a synergist to prepare a composite filler slurry, then adding the slurry to a polytetrafluoroethylene dispersion, and preparing a polytetrafluoroethylene composite membrane through mixing and dispersing, film forming and drying, sintering and winding, wherein: (1) The molecular weight of polytetrafluoroethylene in the polytetrafluoroethylene dispersion is 500,000 to 2,000,000, and the particle size of polytetrafluoroethylene latex is 150 to 220 nanometers; (2) The interface modifier is a non-polar liquid with a molecular weight of less than 1000 and a three-phase contact angle with polytetrafluoroethylene particles and water of less than 90 degrees and is immiscible with water, including polyorganosiloxanes with a molecular weight of less than 1000, long-chain alkanes, fatty alcohols and aromatic alcohols, such as a mixture of one or more of silicone oil, white oil, n-dodecane, octadecanol and terpineol, and the added mass is 0.01-5% of the solid mass in the polytetrafluoroethylene dispersion; (3) The synergist is an oil-soluble material that can increase the viscosity of the above-mentioned interface modifier and is immiscible with water, such as a mixture of one or more of modified hydrogenated castor oil, organic bentonite, hydrophobically modified acrylate, polyisobutylene, polymethacrylate, and ethylene-propylene copolymer, and the added mass is 0-5% of the mass of the interface modifier; (4) The hydrophobic conductive functional filler is a zero-dimensional or two-dimensional conductive functional filler having a hydrophilic contact angle greater than 90 degrees and a conductivity greater than 10 S / m, such as a mixture of one or more of conductive carbon black, silver powder, graphene, and conductive graphite sheets, and the added mass is 0.01-10% of the solid mass in the polytetrafluoroethylene dispersion; (5) The composite filler slurry is prepared by adding an interface modifier, a synergist and a hydrophobic conductive functional filler into a planetary agitator and stirring at a speed of 1000 to 2000 revolutions per minute for 2 to 10 minutes; (6) The mixing and dispersing process comprises the following steps: adding a composite filler slurry to a polytetrafluoroethylene dispersion, stirring the mixture at a speed of 1000 to 2000 revolutions per minute for 2 to 10 minutes using a propeller or planetary agitator, and then stirring the mixture at a speed of 500 to 800 revolutions per minute for 2 to 10 minutes to prepare a polytetrafluoroethylene composite dispersion; (7) The film-forming and drying step is to cast, scrape or spin coat the polytetrafluoroethylene composite dispersion on a suitable substrate material and dry it at a suitable temperature; (8) The polytetrafluoroethylene composite film can be completely peeled off from the base material and rolled up, and the film thickness ranges from 5 to 200 microns.

2. The method for preparing a polytetrafluoroethylene composite film for a friction nanogenerator according to claim 1, characterized in that The particle size of the zero-dimensional conductive functional filler such as conductive carbon black and silver powder ranges from 20 nanometers to 5 micrometers.

3. The method for preparing a polytetrafluoroethylene composite film for a triboelectric nanogenerator according to claim 1, characterized in that The particle size of the zero-dimensional conductive functional filler such as conductive carbon black and silver powder ranges from 20 nanometers to 5 micrometers.

4. The method for preparing a polytetrafluoroethylene composite film for a triboelectric nanogenerator according to claim 1, characterized in that The film forming drying temperature is 20-80 degrees Celsius, and the drying time is 5-60 minutes.

5. The method for preparing a polytetrafluoroethylene composite film for a triboelectric nanogenerator according to claim 1, characterized in that The sintering temperature is 350-400 degrees Celsius, and the sintering time is 10-60 minutes.

6. The method for preparing a polytetrafluoroethylene composite film for a triboelectric nanogenerator according to claim 1, characterized in that The polytetrafluoroethylene composite membrane can be up to 1.5 meters wide and 1000 meters long.